Assessment of Post-traumatic Growth using Post-traumatic Growth Inventory and the Impact of Clinical Pharmacists on Post-Traumatic Growth Enhancement (Asian Journal of Pharmaceutics (AJP), 2025)
This study aimed to evaluate the impact of trauma and assess levels of post-traumatic growth (PTG)among individuals who had experienced traumatic events. Additionally, it sought to explore the effectivenessof clinical pharmacist–led counselling in enhancing PTG levels in individuals with lower initial PTG scores.Materials and Methods: A total of 130 participants, aged between 16 to 80 years, who had experienced traumaat some point in their lives, were included in this study. A mixed-method approach was employed, incorporatingboth qualitative interviews and quantitative assessments. Two standardized tools were used: the Post-Traumatic Growth Inventory (PTGI) and the Impact of Event Scale-Revised (IES-R). Participants underwenttwo counselling sessions led by clinical pharmacists. Pre- and post-counselling PTG levels were compared.Statistical analysis was conducted using a two-way ANOVA, with a P-value < 0.05 considered statisticallysignificant. Results and Discussion: Out of the 130 participants, 56% (73 individuals) exhibited very high levelsof post-traumatic growth (PTG), while 44% (57 individuals) showed moderate PTG prior to counselling. Aftertwosessions of clinical pharmacist-led counselling, a notable improvement was observed in PTG levels, withseveral participants shifting from lower to higher PTG categories. Statistical analysis using two-way ANOVArevealed significant improvements in specific domains of PTG: personal strength (P = 0.03), new possibilities(P = 0.005), appreciation for life (P = 0.04), and total PTG score (P = 0.03). However, no statistically significantchanges were found in the areas of improved relationships (P = 0.127) and spiritual growth (P = 0.5). Theseresults suggest that counselling interventions by clinical pharmacists have a meaningful impact on enhancingpsychological recovery and fostering growth after trauma, particularly in areas related to personal resilience,future opportunities, and life appreciation. Conclusion: The study demonstrates that clinical pharmacists playa significant role in supporting trauma-affected individuals through structured counselling, which can enhancevarious aspects of post-traumatic growth. Targeted pharmacist interventions can lead to meaningful psychologicalimprovements, especially in personal strength, new life opportunities, and overall PTG.